LivHealth E-surveillance App - Badili Innovations Ltd (Google Play, 2020)
LivHealth E-surveillance App facilitates the recording of syndromic symptoms as well as diseases that are reported by community disease reporters (CDRs). The application enables the easy capture and documentation of disease syndromes as well as confirmed diseases that are reported from the communities who are keeping livestock for a living.